The Impact of the Income Uncertainty on the Decision of Dwelling Purchase or Rent - Метельская, Екатерина (Journal of Economic Sociology, 2010)
The author analyzes the influence of the income uncertainty on the individual choice of a life strategy on example of the decision taken about the dwelling purchase or rent a flat. The author claims that this choice has strong correlation with the overall principles of behavior, as well as with the choice for the strategy in professional, emotional, personal and other type of development.